IDENTIFIKASI POTENSI EKOWISATA DI KAWASAN KONSERVASI PULAU JEMUR KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Atmansyah, Atmansyah; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
PulauJemur is located in Rokan Hilir that have natural conditions with high aesthetic value of beach area that became a breeding green turtle (Chelonia mydas)very rare to be found. Drying island also has a wealth of marine life and beautiful coral reefs so it has great potential to serve as an appeal promising ecotourism environment. This study aimed to identify the potential of ecotourism in protected areas PulauJemur Pasir Limau Kapas Rokan Hilir. This study uses observation and interviews and data analysis used in this research is qualitative descriptive analysis. The research showed that the region has the potential of ecotourism PulauJemur be a potential natural vegetation by votes Fandeli (2000) were classified into categories that range between 11-20 species and biota potential falls into the category of being ranged between 6-10 species, and has characteristicslike biota turtle green (Chelonia mydas) which is an endangered species that is included in the category of unique. While the potential of artificial tourism based on interviews related to the availability of facilities and infrastructure to the community PulauJemur region (83,33%) and visitors (65,00%) provide very adequate value. Keywords: Potential, Pulau Jemur, Ecotourism, Conservation.